Preparation method and application of modified Ketjen black

By modifying Kochen Black as the sulfur carrier of Li-S batteries, cobalt and vanadium atoms are modified to form a nanostructure, and combined with sublimation of sulfur to form a composite positive electrode material, the poor conductivity and shuttle effect problems of Li-S batteries are solved, and high capacity and stable cycling performance are achieved.

CN116445012BActive Publication Date: 2025-04-15SHAOXING INST OF NEW ENERGY & MOLECULAR ENG SHANGHAI JIAO TONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310215942.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-04-15
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

During the commercialization process, Li-S batteries face problems such as poor conductivity, shuttle effect, slow conversion reaction kinetics, and sulfur volume expansion, which affect their energy density and life.

Method used

By modifying Ketjen Black (KB) as a sulfur carrier, cobalt (Co) and vanadium (V) atoms are modified to form nanoCo/KB and nanoVCKB materials, combined with sublimation of sulfur to form a composite positive electrode material, inhibiting the shuttle effect and promoting redox kinetics.

Benefits of technology

The high capacity, stable cycle performance and excellent rate performance of Li-S batteries are achieved, the shuttle effect of polysulfide is suppressed, and the utilization rate and conversion efficiency of sulfur are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116445012B_ABST
    Figure CN116445012B_ABST
Patent Text Reader

Abstract

The present application provides a preparation method and application of modified Ketjen black, which belongs to the technical field of electrode materials based on direct conversion of chemical energy into electrical energy by inorganic compounds. Ketjen black is used as a raw material, and an ethanol solution is added to the Ketjen black for ultrasonic dispersion to form a KB suspension. An aqueous solution of a cobalt salt is first added, and an ultrasonic treatment is performed to obtain a precursor. After drying, the precursor is reduced at high temperature to obtain nano Co / KB, which is then added to an aqueous solution of V2O5 for ultrasonic dispersion, and the modified Ketjen black is obtained after centrifugal drying. The obtained modified Ketjen black is mixed with sublimated sulfur, and vacuum heated to obtain a modified Ketjen black / sulfur complex. When this case is used as a battery carrier, the corresponding battery can exhibit a mild shuttle effect, improved sulfur utilization and conversion efficiency, stable cycle performance, and excellent rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method of modified Ketjen black and its application in the preparation of positive electrode materials for Li-S or Na-S batteries, belonging to the technical field of electrode materials for directly converting chemical energy into electrical energy based on inorganic compounds. Background Art

[0002] In the past few years, there has been a surge in research on Li-S batteries as an alternative to lithium-ion batteries (LIBs). However, there are several obstacles to the commercialization of Li-S batteries, including the low sulfur content (5 × 10 -28 S m -1 ) and the poor conductivity of the final discharge products (Li2S2 and Li2S), the shuttle effect of the intermediate polysulfide (PS), and the x , 4≤x≤8) and severe volume expansion (80%) of sulfur during charge and discharge. Among them, the polysulfide shuttle mechanism is the most important mechanism, which directly affects the energy density and life of Li-S batteries. In order to prevent this problem of lithium-sulfur (Li-S) batteries, many people are committed to designing new nanostructured host materials.

[0003] Carbon-based sulfur electrodes are one of the widely studied materials because carbon has high conductivity, good adsorption properties, good mechanical properties, and customizable characteristics. For example, chemical modification of carbon materials by heteroatom substitution has shown some potential for confining LiPS. Compared with physical confinement, chemical binding will effectively anchor LiPS, making it more suitable for enhancing the long-term cycling performance of Li-S batteries. Therefore, it is necessary to use polar materials that can effectively hinder the shuttling process by providing many active polar sites to adsorb LiPS.

[0004] Polar materials used in Li-S batteries include metal oxides (V2O5, MnO2, Al2O3, Fe2O3, etc.), metal sulfides (ZnS, Co9S8, TiS2, MoS2, MnS, etc.), nitrides (VN, etc.) and metal carbides. According to the literature, theoretical calculations and experiments have confirmed the adsorption of polysulfides on vanadium compounds, even single V atoms. V2O5-decorated carbon nanofiber (VCNF) interlayers effectively anchor LiPS through strong chemical bonding.

[0005] For Li-S batteries, in addition to chemical anchoring technology, electrocatalysis has also been studied. Since 2015, a series of electrocatalytic materials have been disclosed. Electrocatalysis not only regulates the deposition of insoluble Li2S, but also accelerates the conversion rate of LiPS. In these electrocatalytic materials, there is a strong interaction between cobalt (Co) and Li2S. The catalytic activity of Co particles promotes the decomposition of Li2S on Co, has a lower decomposition barrier and reduces polarization. The cobalt and graphite porous carbon (Co@GC-PC) positive electrode still maintains 790mAh g after 220 cycles at 0.2C. -1 In addition to Co particles, Co atoms in nitrogen-doped graphene (Co-N / G) have also been reported as electrocatalysts to trigger the surface-mediated reaction of LiPS. Hollow porous carbon spheres decorated with CoO particles and single V atoms endowed with outstanding catalytic ability and excellent adsorption of polysulfides.

[0006] Therefore, an ideal sulfur carrier is needed, which should have a highly conductive framework to activate the electrochemical activity of sulfur, a large volume to store sufficient sulfur and in situ generated polysulfides, abundant adsorption and catalytic sites to suppress the shuttle effect, and a faster conversion reaction of polysulfides. Summary of the invention

[0007] In view of this, the present application provides a modified Ketjen black, which, as a sulfur carrier in the battery structure, can be compounded with sulfur to form a positive electrode material with good composition control, which can not only prevent the shuttle effect and promote the redox kinetics in the battery, but also give Ketjen black abundant interfacial active sites, ensuring ideal electron transfer, and achieving a balance between the adsorption capacity contributed by V and the catalytic ability of Co for insoluble Li2S.

[0008] Specifically, the present application is implemented through the following scheme:

[0009] A preparation method of modified Ketjen black, comprising the following steps: using Ketjen black (KB) as a raw material, adding an ethanol solution to the Ketjen black for ultrasonic vibration to form a KB suspension, first adding an aqueous solution of a cobalt salt, ultrasonically vibrating and centrifuging to obtain a precursor, drying the precursor and placing the precursor in a quartz tube, reducing the precursor at high temperature under a N2 atmosphere to obtain nano Co / KB, and finally adding the precursor to a V2O5 aqueous solution, ultrasonically dispersing the precursor, and drying the nano Co / KB obtained by centrifugation to obtain the modified Ketjen black; wherein the mass ratio of the cobalt salt to the Ketjen black is 1:1 to 1:2, and 8.24×10 -5 ~1.6×10 -4 mol of V2O5.

[0010] The above scheme realizes the mild preparation of modified Ketjen black. Ketjen black is used as raw material, and Ketjen black is modified by vanadium (V) and cobalt (Co) atoms. First, nano Co particles are synthesized in situ, which are mainly confined in the pores of KB. Then V is loaded into the material to obtain modified Ketjen black (VCKB). During the reaction, KB suspension and precursor are used to complete wet impregnation, and then nano VCKB is prepared by high-temperature reduction process to realize the large-scale production of nano VCKB; it can prevent the shuttle effect and promote the redox kinetics in the battery. At the same time, the above modification gives Ketjen black abundant interfacial active sites and ensures smooth electron transfer, which helps to achieve a balance between the adsorption capacity contributed by V and the catalytic activity of Co in improving the conversion product insoluble Li2S.

[0011] Further, as a preference:

[0012] The ethanol solution is obtained by mixing anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 4:1.

[0013] During the formation of the KB suspension, ultrasonic treatment is performed for 10 to 40 minutes at room temperature.

[0014] In the preparation of the precursor, ultrasonic treatment is performed for 1 to 3 hours at room temperature.

[0015] The drying temperature is 55-65° C., and the drying time is 20-40 hours.

[0016] The reaction temperature of the high temperature reduction is 820-880° C., and the reaction time is 1.5-3 hours.

[0017] 0.075 to 0.15 g of V2O5 is added for every gram of Co / KB.

[0018] At the same time, the applicant also provided the application of the modified Ketjen black in the preparation of battery positive electrode materials / carriers. The prepared modified Ketjen black was mixed with sublimated sulfur and heated in a vacuum oven at 155°C for 12 hours, and finally the modified Ketjen black / sulfur composite positive electrode materials VCKBS, VKBS, CKBS, and KBS were collected. After the modified Ketjen black / sulfur composite positive electrode material was mixed and stirred with a binder overnight, an ultrasonic treatment was performed to obtain a positive electrode slurry, which was coated on an aluminum foil as a positive electrode, and assembled with a lithium metal foil as a negative electrode. A 1,2-dimethoxyethane DME:1,3-dioxolane DOL (1:1) solution of 1.0M lithium bis(trifluoromethane)sulfonamide (LiTFSI) and 0.1M lithium nitrate (LiNO3) was used as an electrolyte to obtain a Li-S battery. The E / S of the electrolyte is 20 or 13μLmg -1 .

[0019] The mass percentage of the sulfur in the finished modified Ketjen black is 50 to 80%. More preferably, the mass percentage of the sulfur in the modified Ketjen black is 50 to 70%.

[0020] The vacuum heating temperature is 150-165° C., and the heating time is 10-16 hours.

[0021] The Li-S battery obtained by the above scheme exhibits mild shuttling, improved sulfur utilization and conversion efficiency, and shows stable cycling performance and excellent rate performance. The VCKBS electrode provides 1201 mAh g -1 The initial discharge capacity was 1022 and 985 mAh g after 200 and 300 cycles. -1 The high capacity of Li-S batteries is achieved with a capacity decay of only 0.059% per cycle over 300 cycles and a Coulombic efficiency of 100%. This work represents a sustainable approach to developing highly stable and long-lasting Li-S batteries.

[0022] Further, as a preference:

[0023] The adhesive is formed by dissolving polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solvent, with a mass fraction of 2%.

[0024] The mass ratio of the modified Ketjen black / sulfur composite positive electrode material to the binder is 9:1.

[0025] The battery obtained by the above scheme showed excellent cycling and rate performance, with an initial capacity of 1329 mAh g at 0.1C. -1 Even at higher sulfur loadings (2.4 mg cm -2 ), a high capacity retention of 85% was achieved after 200 cycles at 0.2C.

[0026] The modified Ketjen black / sulfur composite can also be used for the preparation of sodium batteries: the modified Ketjen black / sulfur composite and the binder are mixed overnight in a mass ratio of 9:1, and then ultrasonically treated to obtain a positive electrode slurry, which is coated on an aluminum foil as a positive electrode, and assembled with a sodium metal foil as a negative electrode to obtain a Na-S battery, wherein the electrolyte is a 1.0 M sodium bis(trifluoromethane)sulfonamide solution as an electrolyte, and the E / S of the electrolyte is 20 or 13 μL mg -1 The adhesive is formed by dissolving polyvinylidene fluoride in N-methylpyrrolidone solvent. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the synthesis process of this application;

[0028] Figure 2XRD patterns of VCKBS, VCKB, VKB, CKB and KB prepared in Example 1;

[0029] Figure 3 Raman spectra of VCKB, VKB, CKB and KB prepared in Example 1;

[0030] Figure 4 SEM (a), TEM (b), HRTEM image (c) and elemental map (dh) of VCKB prepared in Example 1;

[0031] Figure 5 High-resolution XPS spectra of Co 2p (a), V 2p (b), Co 2P (c) and V 2p (d) of the CKBS prepared in Example 1;

[0032] Figure 6 The electrochemical performance diagram of CKBS prepared in Example 2 as the Co content changes;

[0033] Figure 7 The electrochemical performance diagram of CKBS prepared in Example 3 as the V2O5 content changes;

[0034] Figure 8 The electrochemical performance comparison chart of VCKBS, CKBS, VKBS and KBS prepared in Example 3;

[0035] Fig. 9 A comparison of the electrochemical performance of VCKBS with different weight percentages of sulfur as the sulfur cathode in Li-S batteries;

[0036] Fig.10 At 0.1C rate and S loading of 1.2 mg cm -2 , E / S ratio is 20 mL g -1 Discharge curves of VCKBS (70 wt%), CKBS, VKBS and KBS as sulfur cathode in five different cycles of Li-S battery;

[0037] Fig.11 The corresponding material is 5 mmol L -1 Comparison of polysulfide adsorption in Li2S6 solution after 24 hours;

[0038] Fig.12 Cyclic voltammograms of VCKBS and KBS;

[0039] Fig.13 EIS spectra of Li-S batteries with KBS, VKBS, CKBS and VCKBS cathodes after 100 cycles (a) and corresponding rate performance (b);

[0040] Fig.14 For KBS and VCKBS cathodes at 0.2C, the sulfur loading is 2.4 mg / cm -2 The cycling performance of Li-S batteries;

[0041] Fig.15 TEM image of VCKB;

[0042] Fig.16 Measured spectra of O1s, C 1s, S 2p and XPS of VCKBS.

[0043] Fig.17 XRD patterns of VCKB prepared with different V2O5 addition amounts;

[0044] Fig.18 This is a thermogravimetric analysis comparison chart of VCKB materials and KBS loaded with different sulfur amounts. DETAILED DESCRIPTION

[0045] 1. Material requirements:

[0046] The modified Ketjen black in this embodiment is prepared by using Ketjen black (KB) as a raw material, adding cobalt salt and V2O5, and then compounding with sublimated sulfur. During the preparation process, analytically pure chemicals are used as materials without further treatment.

[0047] 2. Material characterization:

[0048] (1) X-ray powder diffractometer (XRD) was used at 40 kV and 30 mA (Shimadzu-6000) using Cu Kα radiation. Obtain XRD diffraction data.

[0049] (2) Raman spectra were obtained using a Raman microscope (Thermo Fisher Scientific) with a 532 nm Ar laser.

[0050] (3) The morphology of the synthesized materials was examined using a field emission scanning electron microscope (FESEM, JEOL, JSM-7401F) and a transmission electron microscope (TEM, JEOL-1200) with an accelerating voltage of 5 kV.

[0051] (4) X-ray photoelectron spectroscopy (XPS) was performed on a VG Scientific ESCALAB 220iXL X-ray photoelectron spectrometer.

[0052] (5) TGA was measured using an SDTQ 600 instrument (TA, USA, DSC-TGA) in a nitrogen atmosphere with a temperature range of 25–500 °C and a heating ramp of 5 °C.

[0053] (6) Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) measurements were performed at room temperature using a Biologic SP300 potentiostat / galvanostat.

[0054] In the EIS experiment, the frequency range and voltage amplitude were 10 mHz–100 kHz and 10 mV, respectively. The EIS spectra were fitted to the proposed equivalent circuit model using the “randomization + simplex” method with 1000 fitting and randomization iterations in the Bio-Logic Zfit software. For CV measurements, 0.1 mV s -1 All experiments were performed on three replicate cells and the results presented here are the average of the three replicates.

[0055] (7) The cycle performance of the Li-S battery was measured at different current densities, and the potential window was 1.7-3 V. In this example, the specific discharge capacity was calculated based only on the mass of sulfur.

[0056] Example 1

[0057] Combination Figure 1 , the preparation process of modified Ketjen black in this embodiment is as follows:

[0058] (1) 1.2x10 -1 mol Ketjen black (also known as pure Ketjen black, referred to as KB) was added to 120 ml of deionized water and 30 ml of anhydrous ethanol, and then ultrasonicated for 30 minutes to form a KB suspension; at the same time 3.43x10 -3 mol cobalt salt (Co(NO3)2·6H2O) was completely dissolved in 20 ml of deionized water and slowly added to the KB suspension, which was ultrasonically treated for two hours and centrifuged to obtain the precursor.

[0059] In this process, Co 2+ The ions can penetrate the micropores and mesopores of KB, which is beneficial to the formation of highly dispersed nano-Co particles.

[0060] (2) Dry the precursor in an oven at 60°C for 24 hours.

[0061] (3) The dried precursor was reduced at 850°C for 2 hours in a N2 atmosphere in a quartz tube to obtain nano-Co / KB (CKB).

[0062] (4) V2O5 was dissolved in 40 ml of deionized water, stirred for 2 h, and 200 mg of CKB was slowly added and ultrasonically dispersed for 2 h. Nanomaterial VCKB was obtained by centrifugation.

[0063] (5) The prepared VCKB was mixed with sublimed sulfur and heated in a vacuum oven at 155 °C for 12 h, and VCKBS was finally collected.

[0064] For comparison purposes, KBS, VKBS and CKBS were prepared according to the same procedure as step (5):

[0065] KB was mixed with sublimed sulfur and heated in a vacuum oven at 155 °C for 12 h, and KBS was finally collected;

[0066] VKB was mixed with sublimed sulfur and heated in a vacuum oven at 155 °C for 12 h, and VKBS was finally collected;

[0067] CKB was mixed with sublimed sulfur and heated in a vacuum oven at 155 °C for 12 h, and CKBS was finally collected.

[0068] (6) VCKBS, VCKB, VKB, CKB and binder (2 wt% polyvinylidene fluoride PVDF in N-methylpyrrolidone NMP solution) were mixed in a mass ratio of 9:1, stirred at room temperature overnight and ultrasonically treated for 2 hours to obtain a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil (15 μm thick, MTI) with a scraper and dried in a vacuum oven at 60-80 ° C. The dried electrode was pressed and punched to form a disc with a diameter of 12 mm to obtain a sulfur composite positive electrode. The Li-S button cell was assembled in an argon-filled glove box (O2 and H2O < 0.5 ppm, MBraun), with lithium metal foil as the negative electrode, and 1.0 M lithium bis(trifluoromethane)sulfonamide (LiTFSI) and 0.1 M lithium nitrate (LiNO3) in 1,2-dimethoxyethane DME:1,3-dioxolane DOL (1:1) solution as the electrolyte.

[0069] The XRD patterns of the synthesized VCKBS, VCKB, VKB, CKB composites and pure Ketjen black (KB) are shown in Figure 2. Figure 2 shown.

[0070] Compared with bare KB, Co-containing CKB (JCPDF:15-0806) shows three diffraction peaks (2θ) at about 44.2°, 51.5° and 75.8°, corresponding to the (111), (200) and (220) planes of Co metal, respectively, indicating that the metallic Co phase has been formed. XRD patterns show that VCKB and VCKBS have an amorphous structure.

[0071] The information of chemical bonds can be further analyzed by Raman spectroscopy. Figure 3 shown.

[0072] Carbon at 1584cm -1There is a Raman peak called G peak nearby, which originates from sp 2 E of bond stretching vibration of carbon site 2g Symmetry. Nanocrystalline graphite and amorphous carbon have a wavelength of 1355 cm -1 About (KB here is 1334.2cm -1 ) has an additional peak called the D peak and is derived from the A of the six-fold carbon ring. 1g breathing vibrations. The D mode is forbidden in an ideal graphite structure but appears when disorder increases. The width of the G and D peaks is due to the sp 2 The bonds of the sites are disordered, and the D peak is due only to the six-fold carbon ring. The spectra of all samples are at 1335 cm -1 and 1600cm -1 The DG band is shown nearby. Located at 200-1000cm -1 The VKB peaks at 994 cm-1 and 996 cm-2 are related to the stretching and bending vibrations of different V=O bonds, respectively. -1 The peak at is considered to be the characteristic peak of V2O5, which distinguishes it from other vanadium oxides in Raman spectrum. At the same time, compared with VKB and CKB, there is no additional peak after KB is modified to VCKB. According to calculations, the I D / I G The values ​​are 1.25, 1.13, 1.15 and 1.19 respectively. The I between VCKB and KB D / I G The increase in the value indicates that the overall defect level of the VCKB composite increases, which provides sites for anchoring Co and V and provides channels for the transport of lithium ions and limits the shuttling effect of LiPS to some extent.

[0073] The SEM morphology of VCKB is as follows Figure 4 As shown in a, it can be seen that the KB particles are full, round and evenly distributed.

[0074] Figure 4 b is the TEM image of VCKB, Figure 4 b, 4c and Fig.15 a, b, c in the above. Figure 4 c shows the different lattice fringes of the KB(100) crystal plane with a lattice spacing of 0.34 nm. Figure 4 d shows the HAADF-STEM image of VCKB. Energy dispersive X-ray spectroscopy (EDXS) mapping of the main elements ( Figure 4 e-4h) shows that the element distribution in the whole particle is almost uniform.

[0075] The surface structure and chemical valence of the composites were analyzed by X-ray photoelectron spectroscopy. The corresponding high-resolution Co 2p and V 2p XPS spectra of CKBS, VKBS and VCKBS are shown in Figure 2. Figure 5 As shown, the synthesis of the nanocomposite was confirmed. The high-resolution XPS spectrum of Co 2p showed two peaks at 781.78 eV and 797.2 eV ( Figure 5 a), two peaks at 517.0eV and 524.2eV ( Figure 5 b) V attributed to V2O5 +5 2p 3 / 2 and V +5 2p 1 / 2 . Co 2p spectrum of VCKB ( Figure 5 c) shows characteristic peaks at 780.35 eV and 796.6 eV, attributed to Co(0). By comparing the co-modified material (VCKBS) and the single modified material (CKBS / VKBS), we can see that: the binding energy of Co decreases by 1.43 eV, while the binding energy of V increases by 0.22 eV. This is a typical phenomenon of electronic structure regulation. Co acts as an electron acceptor and V acts as an electron donor. The carbon skeleton is an excellent electron conductor, which can establish an electron transfer bridge between Co and V, leading to the formation of a donor-π-acceptor system. Therefore, the synergistic effect between them brings about a significant enhancement of VCKBS. The entire system fully exerts the role of catalytic sites and adsorption sites through electronic regulation. All corresponding peaks of Co2p and V 2p are also obvious in the high-resolution XPS spectrum of VCKBS nanocomposites. The O1s, C 1s, S 2p and XPS measurement spectra of VCKBS are shown in Figure 2. Fig.16 shown.

[0076] Example 2

[0077] This example has the same configuration as Example 1, except that in step (1), different amounts of Co were used to optimize the cycle performance of the Co / KB precursor to examine its discharge capacity and compare the cycle performance of these batteries. The weight ratios of Co salt to KB were 1:1, 1:1.5, and 1:2, respectively, and the resulting CKBS were named CKBS*, CKBS**, and CKBS***, respectively.

[0078] Combination Figure 6 , we can see that the addition of Co in KB increases the capacity and optimizes the capacity retention rate. The initial discharge capacities of CKBS*, CKBS**, and CKBS*** cathodes are 1280, 1245, and 1009 mAh g, respectively. -1, after 100 cycles at 0.1C, the capacity decays were 0.32, 0.19, and 0.27%, respectively. Under the same conditions, the KBS cathode has a lower discharge capacity (804 mAh g -1 ) and a higher capacity decay (1.96%). This means that Co doping of KB improves the sulfur utilization at the beginning of cycling to some extent; the difference between the initial capacities of CKBS** and CKBS*** is moderate.

[0079] The above experiments also show that the best capacity retention can be obtained using CKBS**, indicating that the reaction is more reversible using CKBS**, probably due to the uniform distribution of the final emission product Li2S.

[0080] Due to the need for high stability or limited capacity decay and good discharge capacity, in the following experiments, we chose CKBS** (the weight ratio of Co salt to KB is 1:1.5) as the precursor to synthesize the material VCKBS for further study.

[0081] Example 3

[0082] The configuration of this embodiment is the same as that of embodiment 1, except that in step (4), the addition amount of V2O5 is 8.24 x 10 -5 mol, 1.23x10 -4 mol and 1.6x10 -4 mol, three different samples were prepared to optimize the V content in the final material. The samples were coded as VCKB(a), VCKB and VCKB(b), and their corresponding XRD patterns are shown in Figure 2. Fig.17 The cycling performance of these positive electrodes is shown in Figure 7 As shown, the S loading is 1.2 mg cm -2 .

[0083] When VCKBS (a) and VCKBS (b) were used as the positive electrode materials, the initial discharge capacities of the two were very similar, with VCKBS slightly higher. When VCKBS was used as the positive electrode material, 1329 mAh g -1 The initial discharge capacity is 1249 mAh g after 100 cycles. -1 , showing a capacity retention of 94%.

[0084] Similar to Co, the amount of V should also be moderate to promote reversibility in the battery while not blocking the cathode surface. Therefore, the optimal composite with moderate content of Co and V was selected, i.e., the weight ratio of Co salt to KB was 1:1.5, and the addition amount of V2O5 was 8.24x10 -5 mol.

[0085] exist Figure 8 In this paper, we compared the cycling performance of VCKBS, CKBS, VKBS and KBS as positive electrode materials. The corresponding charge and discharge curves are shown in Figure 2. Fig.10 As shown. Li-S batteries usually have two discharge platforms. The first discharge platform corresponds to the reduction of elemental sulfur S8 to high-order Li2S x (8≤x≤4)PSs. In the second discharge platform, high-order PSs are reduced to shorter PSs and eventually become insulating Li2S.

[0086] For KB, the capacity of the first platform is the lowest, which means that conventional KB has the lowest sulfur utilization. In addition, the first and second discharge platform capacities continue to shrink, indicating that sulfur reduction is irreversible. When comparing the discharge curves of CKBS and VKBS, it can be seen that the voltage curve of the battery with CKBS positive electrode shows a significant decrease in capacity. In contrast, the profiles of VKBS are almost overlapping, and the second platform capacity decreases slightly.

[0087] For the cells with VCKBS cathode, the synergistic effect of Co and V is evident; even after 50 cycles, the discharge capacity and voltage show only slight changes, demonstrating that the VCKBS electrode can limit the shuttle effect and enhance the reversibility of the electrochemical reaction and sulfur utilization.

[0088] In addition, the potential difference between the charge and discharge plateaus of the VCKBS cathode is significantly smaller relative to its counterparts, indicating lower polarization and better charge and discharge efficiency. As a result, the cycling performance of the battery with the VCKBS electrode is superior; it shows higher capacity as well as better cycling stability, with an excellent capacity retention of 94% after 100 cycles at a rate of 0.1C, while the batteries with CKBS, VKBS, and KBS electrodes retain 80%, 87%, and 49% of their initial capacity, respectively.

[0089] Example 4

[0090] The final optimization of the cathode design is to explore the optimal sulfur mass percentage (S wt.%) in the cathode. Determining the optimal sulfur wt.% is critical to improving system-level performance; since sulfur is insulating, sulfur loading must be maximized without sacrificing discharge capacity.

[0091] The configuration of this embodiment is the same as that of embodiment 1, except that in step (6), the VCKB material is loaded with different amounts of sulfur. Based on thermogravimetric analysis (TGA, Fig.18 ), determine the final weight ratio of sulfur used in VCKBS (50, 60, 70, 80%) and KBS (70%) after vacuum drying, and test their cycling performance.

[0092] Combination Fig. 9The initial discharge capacities of the Li-S cells with VCKBS electrodes are 1285 mAh g at 50 wt% and 60 wt% loadings, respectively. -1 and 1306mAh g –1 The initial specific capacity of VCKBS increases continuously with the increase of sulfur content, reaching 70wt%. However, when the sulfur content is further increased to 80wt%, the cathode exhibits a capacity of 965mAh g -1 In the Li-S battery with 70 wt% sulfur content, the discharge capacity is initially 1329 mAh g -1 After 100 cycles at 0.1C (capacity retention rate of 94%), the discharge capacity slowly decreased to 1249 mAh g -1 This suggests that when the sulfur loading rate is below 70 wt%, the internal space of the KB host can accommodate sulfur, Co and V can fully catalyze the charge transfer of sulfur, and the Co / V mass ratio regulation plays a key role in alleviating LiPS shuttling during cycling.

[0093] The adsorption performance of sulfur hosts is a key factor in suppressing the polysulfide shuttling effect, so the material was added to 5 mmol L -1 The adsorption of materials is achieved in Li2S6 solution.

[0094] Polysulfide adsorption experiment: Li2S6 solution was synthesized by dissolving Li2S and S in the above electrolyte at a molar ratio of 1:5 (Li2S+5S=Li2S6) and stirring at room temperature for 24 hours. The resulting solution contained 5 mmol L -1 Li2S6, for lithium polysulfide adsorption experiments. 2 mL of Li2S6 solution was mixed with 10 mg of the cathode sample. All procedures were performed in an argon-filled glove box.

[0095] Combination Fig.11 , the Li2S6 solution with CKB showed slight decolorization after 24 h, which means that only the presence of Co compounds led to poor adsorption of Li2S6. In contrast, the solutions containing VKB and VCKB were almost colorless. This further proves that the presence of V in the material shows good adsorption of polysulfides, which can firmly suppress the “shuttle effect” and avoid the loss of active materials mentioned earlier.

[0096] VCKBS and KBS are within 0.1mV s -1 The cyclic voltammetry (CV) curve from 2.8 to 1.8 V at a scan rate of Fig.12 As shown. It can be observed that VCKBS shows two positive peaks and one negative peak. The peak at about 2.2 V during the first positive scan is attributed to the breakage of cyclic sulfur molecules and the formation of higher-order polysulfides (Li2S n, 4≤n≤8 is highly soluble in aprotic electrolytes). The following peak at about 1.9 V is related to the further electrochemical reduction of high-order polysulfides to insoluble low-order lithium sulfides (Li2S n , n≤2). Interestingly, only one oxidation peak and one reduction peak were observed for the Li-S battery with KBS cathode. Compared with KBS, the CV curves of the battery with VCKBS showed narrower peaks and smaller peak separation, which is consistent with the result that VCKBS can significantly accelerate the conversion of LiPS. In addition, the VCKBS battery showed a much higher peak current density than KBS, showing better sulfur utilization and excellent catalytic conversion efficiency.

[0097] Fig.13 a shows the EIS spectra of VCKBS, CKBS, VKBS and KBS cathodes, with the inset showing the Z-fit equivalent circuit of the composite, including two resistors (R), a constant phase component (CPE≈Q2) and a Warburg impedance component (W). Re (~R1) represents the interphase contact resistance between the electrolyte and the cathode, and Rct (~R2) represents the charge transfer resistance in the cathode. Q2 represents CPE, which is consistent with Li + It is related to the solid-state diffusion at the interface of the electrolyte and the positive electrode. W2 is the Warburg impedance element attributed to the diffusion of lithium ions in the active material. According to the results obtained by fitting the EIS spectra (Table 1), the R1 and R2 values ​​of all materials are smaller than those of KBS, indicating better charge transfer ability and lower electrolyte electrode interface resistance. Among all the materials, VCKBS exhibits the smallest resistance value, which should be attributed to the synergistic effect of Co and V, resulting in high charge transfer ability due to their high adsorption properties and improved reaction kinetics.

[0098] Evaluation of 0.1 to 1C (1C = 1675mA g -1 ) The rate performance of the composite cathode at different current densities, such as Fig.13 As shown in Figure 2b, the results show that the Li-S battery with KBS exhibits the worst rate performance, while the batteries with VKBS and CKBS show almost similar results. The VCKBS cathode has excellent rate performance due to the enhanced reaction kinetics. When the rate is suddenly switched from 1C to 0.1C again, the original capacity is almost restored, indicating the robustness and stability of the VCKBS cathode material.

[0099] Table 1: Resistance of Li-S batteries prepared with different cathodes

[0100] Sample <![CDATA[R1(Ω)]]> <![CDATA[R2(Ω)]]> <![CDATA[V2O5-Co / KB@S]]> 7.0 30.1 Co / KB@S 7.12 49.90 <![CDATA[V2O5 / KB@S]]> 31.78 54.78 KB@S 32.1 249.8

[0101] At 0.2C, we evaluated the -2) and the long-term stability of VCKBS and KBS electrodes with a lower E / S ratio (13 mL / g), see Fig.14 The VCKBS electrode provides 1201mAh g -1 The initial discharge capacity was 1022 and 985 mAh g after 200 and 300 cycles. -1 The KBS cathode exhibited a high capacity, with a capacity decay of only 0.059% per cycle within 300 cycles and a Coulombic efficiency of 100%. The KBS cathode exhibited a fast capacity decay at a higher rate, with an initial discharge capacity of 466 mAh g -1 .

[0102] In summary, it can be seen that the VCKBS composite material developed in this case has an optimized Co / V mass ratio and good structural control, which can effectively improve the specific capacity and system-level performance of Li-S batteries. This case uses a simple, low-cost high-temperature reduction method to in-situ synthesize nano-metal Co particles in Ketjen Black (KB) pores, and then adds V with excellent physical properties to form a nano-VCKB composite material. The material has good control. The development of the VCKBS composite material enriches the interfacial active sites and high charge transfer rate, and achieves a balance between the adsorption capacity contributed by V and the catalytic activity derived from Co in the material, showing suppressed LiPS shuttling and improved sulfur utilization and conversion efficiency. The corresponding battery exhibits excellent cycle and rate performance, with an initial capacity of 1329mAh g at 0.1C. -1 Even at higher sulfur loadings (2.4 mg cm -2 ), a high capacity retention of 85% was achieved after 200 cycles at 0.2C.

Claims

1. Application of modified Ketjen black in the preparation of positive electrode materials for batteries, characterized in that: Here are the steps: Step 1: Using Ketjen black as a raw material, adding Ketjen black to an ethanol solution and ultrasonically dispersing it to form a KB suspension, first adding an aqueous solution of a cobalt salt and ultrasonically treating it to obtain a precursor, Step 2: After the precursor is dried, it is placed in a quartz tube and subjected to a high temperature reduction reaction at 820-880°C for 1.5-3h in a N2 atmosphere to obtain nano Co / KB. Step 3, adding nano-Co / KB into a V2O5 aqueous solution for ultrasonic dispersion, and then centrifugally drying to obtain modified Ketjen black; The mass ratio of the cobalt salt to Ketjen black is 1:1 to 1:2, and each gram of nano Co / KB corresponds to the addition of 4×10 -3 ~1×10 -1 mol of V2O5; Step 4: The modified Ketjen black obtained in step 3 is mixed with sublimated sulfur and heated in vacuum to obtain a modified Ketjen black / sulfur composite. Step 5: After the modified Ketjen black / sulfur composite and the binder are mixed at a mass ratio of 9:1 overnight, ultrasonic treatment is performed to obtain a positive electrode slurry, which is coated on an aluminum foil as a positive electrode material, and a Li-S battery is assembled with a negative electrode lithium metal foil and a 1.0 M lithium bis(trifluoromethane)sulfonamide solution as an electrolyte. The mass percentage of sulfur in the modified Ketjen black is 50 to 80%. The E / S of the electrolyte is 20 or 13 μL mg −1 , The adhesive is formed by dissolving polyvinylidene fluoride in N-methylpyrrolidone solvent.

2. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: The ethanol solution is obtained by mixing anhydrous ethanol and deionized water, and the volume ratio of anhydrous ethanol to deionized water is 4:

1.

3. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: During the formation of the KB suspension, ultrasonic treatment is performed at room temperature for 10 to 40 minutes.

4. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: During the preparation of the precursor, ultrasonic treatment is performed at room temperature for 1 to 3 hours.

5. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: The drying temperature is 55-65° C., and the drying time is 20-40 hours.

6. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: Each gram of nano-Co / KB corresponds to the addition of 4.12×10 -3 ~8×10 -2 mol of V2O5.

7. The use of a modified Ketjen black in the preparation of a positive electrode material for a battery according to claim 1, characterized in that: The modified Ketjen black / sulfur composite electrode provides 1201 mAh g -1 The initial discharge capacity was 1022 and 985 mAh g after 200 and 300 cycles. -1 The battery has a high capacity, with a capacity decay of 0.059% per cycle within 300 cycles and a Coulombic efficiency of 100%.

8. Use of a modified Ketjen according to any one of claims 1 to 7 in the preparation of a positive electrode material for a battery, characterized in that: In step five, the lithium metal foil of the negative electrode is replaced with a sodium metal foil, and the electrolyte is replaced with a 1.0 M sodium bis(trifluoromethane)sulfonamide solution to assemble a Na-S battery.

Citation Information

Patent Citations

  • Preparation method of multi-element nanometer sulfur anode material for lithium ion battery

    CN1803631A